Measurements of Lung Size in Ultrasound and Magnetic Resonance Imaging in Congenital Diaphragmatic Hernia - A Comparison of Prenatal Imaging Techniques = Messung der Lungengröße mittels Ultraschall und Magnetresonanztomografie bei Kindern mit kongenitaler Zwerchfellhernie – ein Vergleich pränataler Bildgebungstechniken - Schreiner, Yannick; Schmidt, Johannes Lukas; Weis, Meike; Nowak, Oliver Claudius; Kohl, Thomas; Hetjens, Svetlana; Rafat, Neysan; Schaible, Thomas (Ultraschall in der Medizin, 2025)
To investigate the correlation between different prenatal imaging techniques in congenital diaphragmatic hernia (CDH) and their prognostic value. 209 fetuses with CDH were enrolled in this retrospective cohort study. The prenatal ultrasound-based and MRI-based (MRI: magnetic resonance imaging) observed-to-expected lung-to-head ratio (o/e-LHR) and MRI-based relative fetal lung volume (rFLV) were evaluated and compared. Their prediction component with respect to clinical outcome was evaluated. Mean values were compared by two-sample t-tests or the Mann-Whitney U-test. The Chi-square or Fisher’s exact test was used in order to compare qualitative parameters. Kappa coefficients, McNemar test, and Bowker’s test were used to assess the degree of agreement. The study population included 183 fetuses with left-sided and 26 fetuses with right-sided CDH. Survival did not differ significantly (74.3% vs. 80.8%, p=0.053). For every imaging technique, incidences of extracorporeal membrane oxygenation (ECMO) and chronic lung disease decreased, and the probability of survival increased gradually reaching minima and maxima for o/e-LHR and rFLV above 35%. Outcome improved if rFLV was above 35% - compared to MRI-based measurement of o/e-LHR above 35%. Our data confirm the predictive value of o/e-LHR for CDH - irrespective of the diagnostic modality. MRI evaluation of o/e-LHR was not superior compared to sonography. MRI evaluation of rFLV correlated with morbidity and mortality which can be beneficial for fetuses with an otherwise good prognosis based on higher o/e-LHR as 2D imaging techniques can underestimate the fetuses’ risk for pulmonary hypertension and ECMO.
Gesehen am 01.07.2025